Genes associated with virulence and pathogenicity of Rickettsia rickettsii: A systematic review - Cortés Sánchez, Mei Lin; Jiménez Vega, Florinda; Escárcega Ávila, Angélica María (Horizonte Sanitario, 2025)
Objective: To review recent literature on the function of genes associated with virulence and pathogenicity in Rickettsia rickettsii. Materials and Methods: This systematic review followed the PRISMA 2020 guidelines for systematic reviews. Searches were conducted in Google Scholar and PubMed (2015–2025) using keywords and Boolean operators related to the topic. Results: A total of 5,026 articles were identified. Ultimately, 50 were selected for the preparation of this review. From these, information was obtained regarding the relevance of virulence-associated genes (Adr1, Adr2, RARP2, RapL). Concerning genes associated with bacterial pathogenicity, OmpA, OmpB, Sca2, Sca4, tlyA, tlyC, pld, RLip, and RickA were reported. These genes are necessary for cell interaction, adhesion, and invasion, as well as immune system evasion. Conclusions: Rickettsia rickettsii is a pathogen of public health importance globally and in Mexico. Therefore, key bacterial genes such as Sca2, Sca4, tlyA, tlyC, RARP2, RapL, Adr1, Adr2, pld, OmpA, and OmpB that influence host interaction and immune evasion were analyzed. However, the strains present in Mexico still require in depth study, and strategies for the prevention, control, and treatment of the disease need to be improved. Keywords: Rickettsia rickettsii; outer membrane proteins; genes; virulence; pathogenicity; surface cell antigens (Sca).